The Civic Music Association Presents Rudolf Serkin Pianist In Concert, New York, NY (Civic Concert Service; New York, 2020)
Program of a concert by Rudolf Serkin in New York, date unknown. The program included a performance of Beethoven's "Waldstein" Sonata, op. 53. Autographed in pencil by the artist. Includes brief program notes.